MEMANFAATKAN SISTEM OPERASI LINUX UNTUK KEAMANAN DATA PADA E-COMMERCE - ., Isnania (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
E-commerce is one of the major networks to do the transaction, where security is an issue that must be considered vital to the security of customer data and transactions. To realize the process of e-commerce, let prepared operating system (OS) that are reliable to secure the transaction path and also Dynamic Database back end that provides a product catalog that will be sold online. For technology, we can adopt open source technologies that are all available on linux. On linux its too bundles Apache web server that integrates with SSL technology (Secure Socket Layer) server and email facilities (able to use sendmail, small or qmaill) and also has the availability of MySQL Database. For the front end we can use Perl, C and PHP which has been used about 1,000,000 Website / sereer in the world. SSL technology (Secure Socket Layer) encryption method, wherein the method is a mathematical method to randomize the information submitted. SSL also supports the identification of even complex digital systems. Keywords: SSL (Secure Socket Layer), E-commerce, Linux, Firewall, Web server